Analisis Keefektifan Kalimat pada Artikel dalam Blog Futureskills Edisi November 2024 sebagai Sumber Bacaan bagi Mahasiswa - Zacki Mahendra; Nabilla Pramita Sari; Rijal Muttaqin; Dito Yus Dermawan; Rochpriyati Rochpriyati; Dwika Tiofahma Ashari; Asep Purwo Yudi Utomo; Tri Astuti (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This research is based on the importance of using effective sentences in educational articles as reading sources for students. Futureskills blog, a widely accessed digital literacy platform, contains articles that need to be evaluated for their linguistic quality, especially in the aspect of sentence effectiveness. The purpose of this research is to analyze sentence effectiveness in Futureskills articles from the November 2024 edition and identify the most dominant types of errors. This research applies a descriptive qualitative approach using observation and note-taking techniques, along with distributional analysis methods. The results show that out of eight analyzed articles, 165 sentences were ineffective, while only 85 sentences were categorized as effective. The most mistakes lie in the inaccuracy of word choice, the use of foreign languages, and word excess. This research provides practical benefits for writers of educational articles in improving language skills, as well as for students as a guide to choosing quality reading. It is hoped that the results of this analysis will also become a reference in preparing scientific articles that are more communicative and effective.